Pemanfaatan media fermentasi kotoran kuda dalam perbanyakan Alona sp. - Mutiara Hariawan; Henneke Pangkey; Jeffrie F. Mokolensang; Cyska Lumenta; Indra R.N Salindeho; Juliaan Ch. Watung (Universitas Sam Ratulangi, 2023)
The purpose of this study was to analyze the effectiveness of fermented horse manure media for the propagation of Alona sp. The research took place at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Sciences, Sam Ratulangi University, Manado. The study used an experimental method with 12 experimental units, consisting of treatment A: fermented horse manure with EM4 solution, treatment B: unfermented horse manure, treatment C: yeast (5 ppm), and treatment D: water. Each experimental unit was inoculated at the initial stage by 10 Alona sp. which is placed in a glass jar with a volume of 500 ml. The water quality of Alona sp. culture media was measured including temperature, DO, and pH. The results of propagation of Alona sp. according to the analysis of variance, it was found that the differences in treatment between the culture media had a significant effect. The results of the BNJ follow-up test showed that treatment A was significantly different from treatments B and D, but not significantly different from treatment C. Water quality measurements on day 6 to day 15 for treatments A, B, C, and D ranged from temperature, 26.3-27.3Â°C, DO 6.5-7.3 ppm and pH 6.2-6.5. Keywords: life food, horse manure, fermentation, aquaculture